The Meanings and The Myths Behind The JKT48 Kiii Team Ã¢â‚¬Å“Jangan Kasih K3ndorÃ¢â‚¬Â Show at The Seskoal Indoor Basketball Building - Arista, Amanda Dwi (Harmonia: Journal of Arts Research and Education, 2019)
The purpose of this study is to find out the meaning of the show seen from within the actors, namely the clothing used on the show Ã¢â‚¬Å“Jangan Kasih K3ndor.Ã¢â‚¬Â The research method used was a qualitative method using Roland BarthesÃ¢â‚¬â„¢ Semiotics theory. Data collection techniques used in this study were primary and secondary data; the data then processed and sorted into research-related data. The results showed that the meaning of the show Ã¢â‚¬Å“Jangan Kasih K3ndorÃ¢â‚¬Â was that there is a message behind every hard work that can realize any dreams so that it became an extraordinary show and appreciated by people. This research also showed there were a lot of meanings, when the show took place, seen from the inside and outside of the actors. The significance of fashion in this performance was very influential and influenced the success of the concert held.